Melatonin partly reverses differentiation and apoptosis resistance caused by chemical hypoxia - XIAO LIU; HUI LIU; YINLIANG QI; SUMEI ZHANG; YINGCAI MA (Nusantara Bioscience, 2025)
Abstract. Liu X, Liu H, Qi Y, Zhang S, Ma Y. 2025. Melatonin partly reverses differentiation and apoptosis resistance caused by chemical hypoxia. Nusantara Bioscience 17: 178-184. Hypoxia, a condition characterized by a deficiency of oxygen reaching tissues, is a key feature of malignant solid tumors. Tumor cells under a hypoxic microenvironment exhibit more malignant phenotypes to adapt to the hypoxic environment for survival by regulating gene expression involved in cell proliferation, differentiation, invasion, migration, angiogenesis, and also chemoresistance. Melatonin is a hormone that has been proven to induce apoptosis and differentiation in various types of malignant cells. The present study aims to investigate the role and potential molecular mechanism of melatonin in mediating chemical hypoxia-induced differentiation and apoptosis resistance. Cobalt chloride (CoCl2) was used to generate an in vitro hypoxia culture model, as verified by the increased expression of hypoxia-inducible factor-1?. The cells treated with melatonin and CoCl2 were collected to determine differentiation and apoptosis levels through LDH (Lactate Dehydrogenase) activity measurement and Hoechst staining. GRP78, p53, and endocan levels were detected using Western blot and ELISA (Enzyme Linked Immunosorbent Assay) to elucidate the potential molecular mechanisms by which melatonin induces differentiation and resistance to apoptosis in response to chemical hypoxia. The significant elevation of a hypoxia marker protein successfully demonstrated (CoCl2-induced hypoxia). The chemical hypoxia environment resulted in a less differentiated phenotype and a lower apoptotic ratio in gastric cancer cells. Melatonin converted the differentiation and apoptosis resistance phenotypes in CoCl2-treated gastric cancer cells. Changes in the expression of endocan, LDH, p53, and GRP78 were observed. Melatonin-regulated differentiation and apoptosis-related genes partly reverse differentiation and apoptosis resistance caused by chemical hypoxia induced by CoCl2. The study provides a new perspective on the anti-tumor effect of melatonin.